2010
DOI: 10.4314/sajas.v39i1.61210
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breed type and lactation status on reproductive performance in

Abstract: This study was conducted to evaluate the effect of breed types and lactation status on reproductive performance of hormonally-treated Awassi ewes. A total of 282 ewes were treated with intravaginal progestagen sponges and equine chorionic gonadotropin. Ewes were mated with fertile rams following sponge removal. Lambing rate was similar between brown-and black-faced ewes, while the percentage of multiple births, fecundity and prolificacy were greater in black-faced ewes. Lambing rate and the percentage of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…This study could not find any significant differences for the onset of oestrus. These results were however, different to that observed by Kridli et al (2009), in brown and black faced Awassi ewes. Nonetheless, it appears that the onset of oestrus following oestrus synchronization occasionally depends on the protocol used (Uriol et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study could not find any significant differences for the onset of oestrus. These results were however, different to that observed by Kridli et al (2009), in brown and black faced Awassi ewes. Nonetheless, it appears that the onset of oestrus following oestrus synchronization occasionally depends on the protocol used (Uriol et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…There was a breed variation for conception rate, with Zulu and Bapedi performing better than that of Namaqua Afrikaner and Damara. Results found between Bapedi sheep and Zulu sheep were similar to that reported previously by Kridli et al (2009); Zeleke et al (2005) and Mansur et al (2018) where lambing rate could not differ among breeds and their lactation statuses. The conception and lambing rate of Zulu sheep and Bapedi sheep were comparable to Farrag (2019) results who reported that, oestrus synchronization result in higher conception rate on the Abou-Delik sheep.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that increasing prolactin concentration due to stimulations during the lactation period has a suppressive effect on gonadotropins and therefore breeding activity is inhibited by the negative effect of pulsatile LH release and the first LH peak in suckling or lactating ewes (21). Another study (22) revealed that lactating ewes that were not suckling their lambs and were at least 90 days in milk had high lambing rates (85.5%). It is suggested that the lower lambing rates obtained in this study may be due to the lactation status or the continuation of suckling.…”
Section: Discussionmentioning
confidence: 99%
“…The application of estrus synchronization programs has been well-documented since the 1970s. In small ruminants, estrus synchronization is achieved either by reducing the length of the luteal phase of the estrous cycle with PGF 2α or by extending the cycle artificially with exogenous progesterone or more potent progestagens (Kusina et al, 2000 andKridli et al, 2009). Particularly that the ability to synchronize the time of breeding and lambing and the achievement of high fertility at first service is highly beneficial for farmers (Gonzalez-Bulnes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%